ANALISIS FAKTOR-FAKTOR KESULITAN BELAJAR MATA PELAJARAN ILMU PENGETAHUAN SOSIAL PADA SISWA KELAS V DI SD INPRES BERTINGKAT MAMAJANG II KOTA MAKASSAR - Sri Hastuti; Suwardi Annas; Alin Liana (Jurnal Ilmiah Pena: Sains dan Ilmu Pendidikan, 2021)
This study aims to 1) determine the factors of learning difficulties in social studies subjects, 2) determine the solutions that can be given in dealing with learning difficulties in social studies subjects. This research is a qualitative research conducted at SD Inpres Bertingkat Mamajang II with the subject of the research is class V with high, medium and low social studies ability categories. The data were collected by using in-depth interviews, observation and documentation. The data analysis technique uses descriptive analysis techniques through data reduction, data display and data verification, while the validity of the data uses credibility, time triangulation, transperability, dependability, and confirmability. The results obtained were 1) Internal factors difficulty in learning come from student interest, motivation, and intelligence; External factors difficulty in learning are including the learning process and inadequate facilities / infrastructure. 2) Solutions to overcome student learning difficulties by increasing student interest and motivation in learning, carrying out a creative learning process, providing adequate supporting facilities / infrastructure for social studies learning. Keywords: Difficulty Learning Social Sciences